The Profile and Triggering Factors of Melasma Patients: A Retrospective Study - Putri Brillian Betrista Viorizka; Trisniartami Setyaningrum; Ema Qurnianingsih; Damayanti (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Melasma is a skin pigmentation disorder characterized by brownish hyperpigmented lesions with symmetrical distribution and irregular borders. It becomes a cosmetic problem that causes a negative impact on quality of life and a lack of confidence in patients. The etiology of melasma is not completely understood, but several factors that trigger melasma can be explained. Yet, the profile and triggering factors associated with the prevalence of melasma patients in Surabaya are still unexplored. Purpose: To determine the profile and triggering factors of melasma patients in the Dermatology and Venereology Outpatient Unit of Dr. Soetomo General Academic Hospital Surabaya from January to December 2019. Methods: A retrospective descriptive study using data from medical records with a total sampling technique. Result: In this study, most of the melasma patients were female (97.5%), dominated by the age group 46-55 years (49.4%), and worked as housewives (40.74%). The triggering factors found in patients were sun exposure (96.3%), cosmetics (67.9%), hormonal (49.4%), and family history (22.2%). The physical examinations of melasma lesions showed that they were mostly located in the malar area (72.8%), light brown colored (74.7%), and 2.0 – 4.0 cm in size (54.3%). Wood's lamp examination showed that most of the lesions had firm and indistinct borders (55.6%). Conclusion: The triggering factors of melasma are multifactorial, but we suspect that sun exposure plays an important role in affecting melasma.